CONSIDERATION OF THE MATARAM RELIGION JUDGES IN DETERMINING THE LEVEL OF MUT'AH AND NAFKAH IDDAH IN DIVORCE (TALAK) CASE, (Case Analysis No. 0041/Pdt.G/2018/Pta.Mtr and No. 0081/Pdt.G/2018/Pta.Mtr) - Samsudin Samsudin (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2019)
Judges' considerations often do not provide satisfaction and do not provide a sense of justice to the parties. The decision of the judge of the Religious High Court is considered the final place, although it can submit an appeal to the Supreme Court which is the highest institution in the area of ??the religious court, so the researcher raises this title and formulates the problem that is the direction of the research. This study aims to find out how the judge's judgment and whether the judges of the Mataram High Court in determining the level of mut’ah and livelihood in the divorce case have fulfilled the principles of justice, usefulness, and legal certainty. The type of research used is qualitative research. Data collection techniques use study decisions, documentation, and interviews. In addition, the data obtained are informants' information, documentation, and are not numbers. Based on the results of the study, the results obtained are as follows: 1) The consideration of the judges of the Mataram High Court in determining mut’ah levels and iddah livelihoods on divorce cases is observing from work, income, wife who is not incoherent and also to the old wife accompany her husband in fostering a family. 2) whereas regarding the decision of the judges of the Mataram High Court in determining the level of mut’ah and livelihood of the iddah in divorce cases the principles of justice and legal usefulness has not yet been fulfilled, the judge is more focused on the principle of legal certainty and the fulfillment of rights and obligations. However, the amount determined is not in accordance with the sense of justice and certainly will not be fulfilled. In its decision, the judge saw the Law, Compilation of Islamic Law (KHI), Islamic Sharia (Al-Qur'an and Hadith), Perma Number 03 of 2017, and Circular of the Supreme Court of Republic of Indonesia Number 1 of 2017.